Text4Support Mobile-Based Programming for Individuals Accessing Addictions and Mental Health Services—Retroactive Program Analysis at Baseline, 12 Weeks, and 6 Months - Noble, Jasmine M.; Vuong, Wesley; Surood, Shireen; Urichuk, Liana; Greenshaw, Andrew J.; Agyapong, Vincent I. O. (Frontiers in Psychiatry, 2021)
Objective: The following provides a preliminary analysis of the Text4Support program, a text-messaging intervention using the principles of cognitive behavioural therapy, which seeks to support the health and wellbeing of individuals seeking support for addiction or mental health concerns. The goal of this study was to assess whether the Text4Support program improved the overall mental well-being of participants. Methods: The evaluation analyzes the experience of individuals who were enrolled in the Text4Support program beginning in July 2019, who had completed the 6-month program by May 2020. Participants were asked to provide responses to three surveys during their time in the program - at baseline, 12-weeks and 6-months, which included questions documenting demographic information, as well as the Clinical Outcomes Routine Evaluation System (CORE-10) – a validated brief 10-item assessment and outcome measurement tool drawn from CORE-OM, in addition to questions pertaining to general satisfaction with the program. Results and Conclusions: This data set did not include a large enough sample of participants to reach statistical significance. Nevertheless, the study provides some preliminary analysis, and identifies opportunities for the future analysis and research.